2012
DOI: 10.1097/00001756-201207110-00003
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-320 induces neurite outgrowth by targeting ARPP-1

Abstract: MicroRNAs are important in central nervous system development, functioning, and pathophysiology. Here we demonstrate that increasing levels of microRNA 320 (miR-320) for 3 days markedly increases neurite length and at 4 days reduces total cell number in N2A cells. In silico analysis of possible miR-320 targets identified cAMP-regulated phosphoprotein-19 kDa (ARPP-19) and semaphorin 3a (Sema3a) as potential targets that could be involved. ARPP-19 was validated by demonstrating reduced mRNA and protein levels wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…30 ARPP19 was predicted and validated as a direct target of miR-320 in neurite and miR-320a regulates tamoxifenresistant in breast cancer cells through targeting ARPP19. 29,36 We confirmed that miR-802 negatively regulated ARPP19 expression in GC cells by transfection with miR-802 mimics. Conversely, ARPP19 overexpression could partially reverse the inhibitory function of miR-802 in GC cell proliferation, migration, and invasion.…”
Section: Discussionsupporting
confidence: 56%
“…30 ARPP19 was predicted and validated as a direct target of miR-320 in neurite and miR-320a regulates tamoxifenresistant in breast cancer cells through targeting ARPP19. 29,36 We confirmed that miR-802 negatively regulated ARPP19 expression in GC cells by transfection with miR-802 mimics. Conversely, ARPP19 overexpression could partially reverse the inhibitory function of miR-802 in GC cell proliferation, migration, and invasion.…”
Section: Discussionsupporting
confidence: 56%
“…Another exciting possibility with miRNAs is targeting plasticity and recovery after the acute phase of stroke. miRNAs have been shown to be critical in neuronal development, and there is potential that plasticity could be increased following stroke by, for example, encouraging neurite outgrowth using miRNAs such as miR-320 (186). Whereas pretreatment using miR-181a (130) and miR-29a (133) was effective in focal and global cerebral ischemia in rodents, testing treatment after the onset of ischemia is an essential step for the development of acute stroke treatment.…”
Section: Mirnas and Mitochondrial Protective Proteinsmentioning
confidence: 99%
“…miR-320 has been shown to be involved in growth, proliferation, and the cell cycle by targeting different genes in different cell lines (31,32). However, the functions and mechanisms of miR-320 in GC function during follicular development remain unclear.…”
mentioning
confidence: 99%